Consensual attending. Issue 1 (March 2020) - Rivers, Nathaniel A
Consensual attending addresses the ecological and relational conditions in which any act of assent or dissent materializes. I argue that consent is not an act undertaken by individuals, but is a relational endeavor that individuates. Any solitary act of assent—of thinking, perceiving, feeling—is predicated upon prior and ongoing consensual acts. The terms of consensual attending modulate one another: consensual distributes attention beyond the individual and attending intensifies the consensual in marking how our joint and collective attention individuates us as sensing beings. Consensual attending is predicated not upon individual rhetorical acts of assent but ambient formations in which rhetorical capacities emerge. To arrive at such a consent, I retune William James' articulation of attention as a function of agreement by looking toward ecologies of attention. This retuning necessarily entails thinking through the ethical and political implications of consensual attending in our present political moment, wherein the virality of #resist and #metoo registers anxiety about our individual and collective (in)capacities to dis/agree. I engage feminist scholarship on consent in the context of sexual relations in thinking through the contextual composition of consent. Thinking through scholarship on sexual consent complicates consensual attending, and addressing sexual consent itself serves as an example of the trouble lurking in the reduction of consent to assent. Such a reduction leaves unaddressed the ecologies in which such collective capacities are composed. I conclude by returning to attention in order to speculate how such consensual capacities might be composed.